2006
DOI: 10.1089/thy.2006.16.1215
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor (ER)-β, But Not ER-α, Is Present in Thyroid Vessels: Immunohistochemical Evaluations in Multinodular Goiter and Papillary Thyroid Carcinoma

Abstract: This study demonstrated that ER-beta, but not ER-alpha, IR is present in the endothelium of thyroid vessels. Furthermore, although data need to be confirmed in larger observations, these results suggest the lack of differences in the pattern of vascular ER-beta IR between MNG and PTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 32 publications
4
14
1
2
Order By: Relevance
“…Although in our study we did not noted any significant differences in ER expression between GD and NG, we may not directly compare our results with the results obtained www.fhc.viamedica.pl by Wang et al as the ER expression of ER was not studied in NG lesions [20]. The results of studies analyzing ER expression in NG were inconsistent, as some studies reported even higher ER expression as this noted in our studies, whereas some did not report ERa expression in thyrocytes [21][22][23]. Studies aimed at examining the associations between ER and GD found, that the ESR2 gene was not associated with GD incidence in the Japanese population [24], whereas in the Polish study of Kisiel et al, the authors found a significant association between this gene and GD susceptibility [1].…”
Section: Discussioncontrasting
confidence: 89%
“…Although in our study we did not noted any significant differences in ER expression between GD and NG, we may not directly compare our results with the results obtained www.fhc.viamedica.pl by Wang et al as the ER expression of ER was not studied in NG lesions [20]. The results of studies analyzing ER expression in NG were inconsistent, as some studies reported even higher ER expression as this noted in our studies, whereas some did not report ERa expression in thyrocytes [21][22][23]. Studies aimed at examining the associations between ER and GD found, that the ESR2 gene was not associated with GD incidence in the Japanese population [24], whereas in the Polish study of Kisiel et al, the authors found a significant association between this gene and GD susceptibility [1].…”
Section: Discussioncontrasting
confidence: 89%
“…However, similarly, the patterns of ERa and ERb expression in thyroid carcinoma tissues are widely varying. Some authors did not observe ERa immunostaining in thyroid adenomas, goiters, and papillary, follicular, and anaplastic thyroid carcinomas, but ERb immunoreactivity in all benign and malignant thyroid samples (Ceresini et al 2006, Vaiman et al 2010a. In contrast, others reported an increased expression of ERa in PTC tissues in comparison to low or absent expression in normal thyroid tissues (Chen et al 2008, Kansakar et al 2009).…”
Section: Er Expression In Benign and Malignant Thyroid Tissuesmentioning
confidence: 96%
“…Benign and malignant thyroid cells and tissues express functional oestrogen receptors (ERs) and their growth is stimulated by oestrogen (Furlanetto et al 1999, Manole et al 2001, Ceresini et al 2006, Kumar et al 2010, Rajoria et al 2010, Di Vito et al 2011. In addition, the presence of these receptors has also been demonstrated in thyroid vessels that may be relevant for the vascularization of neoplastic tissues (Ceresini et al 2006).…”
Section: Introductionmentioning
confidence: 99%